Biosorption of Pd(II) from Aqueous Solution using Leaves of Moringa oleifera as a Low-cost Biosorbent - Dinani Amorim; Bruno Costa; Denis Martinez (Bioactivities, 2023)
Palladium ion (Pd(II)) is one of the hazardous metal pollutants commonly found in industrial effluents and poses severe environmental and human health impacts. The present study has chosen the leaves of Moringa oleifera (L-MO) as a potential biosorbent for removing Pd(II) from the aqueous solution. Various parameters such as pH, biosorbent dose, and initial Pd(II) concentration were optimized for maximum removal of Pd(II) using standard protocols. The Fourier-transform infrared spectroscopy study was performed to identify the functional groups involved in Pd(II) biosorption mechanism. The analysis of FTIR spectra confirmed the involvement of functional groups such as C–O, C=O, C–H, and O–H in the biosorption of Pd(II) on the surface of L-MO. The biosorption of Pd(II) was highest at pH 6. The sorption equilibrium data were well-fitted with the Langmuir isotherm model (R2 = 0.9896). The highest adsorption capacity of L-MO was 41.15 mg/g. It is concluded that the L-MO could be used as a potentially low-cost novel biosorbent to remove Pd(II) from contaminated water.